2013
DOI: 10.7213/academica.011.002.ao07
|View full text |Cite
|
Sign up to set email alerts
|

INFLUÊNCIA DO MANEJO PRÉ-ABATE SOBRE A FREQUÊNCIA DE LESÕES E CARACTERÍSTICAS DAS LESÕES DE CARCAÇAS BOVINAS ABATIDAS NO SUL DO PARÁ Influence of pre-slaughter management on the frequency of injuries and characteristics of bovine carcasses from Southern Pará State, Brazil

Abstract: As preocupações dos consumidores sobre bem-estar animal e a qualidade dos alimentos estão fortemente presentes na atualidade. A qualidade da carcaça pode ser comprometida por contusões que ocorrem durante o processo do manejo pré-abate. Objetivou-se avaliar o manejo pré-abate, relacionando a frequência de lesões presentes nas carcaças bovinas na região sul do Pará. As lesões foram encontradas mais frequentemente em quartos traseiros (73,68%), sendo classificadas na maioria das vezes como contusões recentes (90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…It still is the cause of large financial losses, which was R$ 72,219.05. Pereira et al (2013) mentioned a lesions' rate of 73.68% by bruise in bovine carcasses and Hensi et al (2014) reported 74.6%, with a loss of R$ 387,554.67. Other renal diseases such as uronephrosis, nephritis and renal calculi represented negligible economic losses.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…It still is the cause of large financial losses, which was R$ 72,219.05. Pereira et al (2013) mentioned a lesions' rate of 73.68% by bruise in bovine carcasses and Hensi et al (2014) reported 74.6%, with a loss of R$ 387,554.67. Other renal diseases such as uronephrosis, nephritis and renal calculi represented negligible economic losses.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%